2022
DOI: 10.1364/oe.447172
|View full text |Cite
|
Sign up to set email alerts
|

Quantum cascade laser absorption spectrometer with a low temperature multipass cell for precision clumped CO2 measurement

Abstract: We present a quantum cascade laser-based absorption spectrometer deploying a compact (145 mL volume) segmented circular multipass cell (SC-MPC) with 6 m optical path length. This SC-MPC is embedded into an effective cooling system to facilitate operation at cryogenic temperatures. For CO2, the sample is cooled to 153 K, i.e. close to the sublimation point at 10 mbar. This enables efficient suppression of interfering hot-band transitions of the more abundant isotopic species and thereby enhances analytical prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Finally, due to its versatility, our approach can be extended to rare isotopic species of simple molecules such as clumped CO 2 (already demonstrated by Nataraj et al), CH 4 , or N 2 O and other volatile organic compounds, thereby opening new perspectives in environmental sciences and fundamental research.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Finally, due to its versatility, our approach can be extended to rare isotopic species of simple molecules such as clumped CO 2 (already demonstrated by Nataraj et al), CH 4 , or N 2 O and other volatile organic compounds, thereby opening new perspectives in environmental sciences and fundamental research.…”
Section: Resultsmentioning
confidence: 86%
“…QCLAS Setup. The spectrometer is an adaptation of a previous setup described in detail by Nataraj et al 17 A schematic of the optical setup is shown in Figure 2. Briefly, it uses a distributed feedback quantum cascade laser (DFB-QCL, Alpes Lasers) as light source emitting in the spectral region around 1385 cm −1 .…”
Section: T H Imentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Recent work has demonstrated that laser spectroscopy circumvents these challenges and is a promising method for accurate clumped isotope measurements of CO 2 and other gases. [18][19][20][21][22][23][24][25][26] Compared to IRMS systems, laser spectrometers are nondestructive, highly sensitive, and efficient, which makes them ideal for high-throughput, precise clumped isotope measurements. As each isotopologue of CO 2 has a unique absorption spectrum, laser spectrometers can directly measure single isotopologues (e.g., 16 O 13 C 18 O) and remove the need for and uncertainty with correcting for mass contributions from "unwanted" isotopologues.…”
mentioning
confidence: 99%
“…The main analytical challenge of methane isotopologues analysis is the requirement for high analytical accuracy, generally in the sub-per-mille range, at low relative abundances. Measurements of 13 CH 4 / 12 CH 4 ratios are routinely performed with commercial tunable mid-IR laser direct absorption and cavity-ring down spectrometers at atmospheric abundances, , while 12 CH 3 D/ 12 CH 4 analysis in ambient air requires precedent preconcentration. , In the case of doubly substituted isotopologue analysis, there are currently two competing analytical techniques, both applied on pure or high-concentration samples: high-resolution isotope ratio mass spectrometry (HR-IRMS) , and quantum cascade laser absorption spectroscopy (QCLAS). To date, both methods are capable of achieving precision of better than 0.1‰ and 1‰ for Δ 13 CH 3 D and Δ 12 CH 2 D 2 , respectively.…”
mentioning
confidence: 99%